Evaluation Of Domestic Sludge As A Nutritional Source For Maize (Zea Mays L.) Under Kashmir Temperate Conditions (Applied Biological Research, 2013)
Several sewage treatment plants have recently been constructed in Srinagar city  (Jammu & Kashmir) around the famous Dal lake but without any proper sewage  management consideration. Land-fill as sludge disposal option is not so attractive  due to the space limitation in the city. However, recycling sludge for agricultural  use may not only serve as an ecofriendly and safe route for sludge disposal but  also may improve soil health. Field trials were conducted at Agricultural Research  Farm, Krishi Vigyan Kendra, SKUAST-K, Shuhama, Srinagar during kharif  seasons of 2008-09 and 2009-10 to evaluate the effect of integrated use of locally  generated sludge and chemical fertilizers on maize productivity and soil fertility.  Highest maize grain yield (4630 kg ha-1), stover yield (7270 kg ha-1) and nutrient  contents in grain (15.5 g N, 4.3 g P, 4.8 g K, 32.1 mg Zn, 2.5 mg Cu, 8.5 mg Mn  and 26.1 mg Fe kg-1) and stover (6.2 g N, 1.4 g P, 17.2 g K, 39.3 mg Zn, 5.2 mg Cu,  44.8 mg Mn and 242.7 mg Fe kg-1) were found in treatment 75% of recommended  NPK + 30 t sludge ha-1. This was followed by statistically at par treatments of  100% recommended NPK + 15 t sludge ha-1, 75% recommended NPK + 15 t  sludge ha-1 and 50% recommended NPK + 30 t sludge ha-1. Significantly high N,  P, K, Zn and Fe uptake by the crop was observed in 75% recommended NPK +  30 t sludge ha-1 treatment in comparison to other treatments. The treatments  receiving sludge significantly improved organic carbon, available macro-nutrients  and DTPA-extractable micro-nutrientsin soil over 100% NPK. The study revealed  that the integrated use of sludge @ 15 t ha-1 + 75-100% recommended NPK or sludge @ 30 t ha-1 + 50-75% recommended NPK may help in sustaining maize yield and improving soil health under climatic conditions of Lesser Himalayas.
Keywords: Chemical fertilizers; domestic sludge; integrated nutrient use; soil health; yield